Dynamics of Coral Fish Biomass in The Coastal Waters of Spelman Strait, Central Buton Regency, Southeast Sulawesi - Muis, Muis; Mustafa, Ahmad; Ramlah, Ramlah (Jurnal Laut Pulau: Hasil Penelitian Kelautan, 2024)
The coastal waters of the Spelman Strait are rich in reef fish resources. Small-scale fishers also use coral fishing in the coastal waters of the Spelman Strait in meeting household needs and improving their welfare. The purpose of this research is to analyze how coral fish biomass in two fishing seasons, namely the west and east seasons. The coastal waters of the Spelman Strait are rich in reef fish resources. Small-scale fishers also use coral fishing in the coastal waters of the Spelman Strait in meeting household needs and improving their welfare. The purpose of this research is to analyze how coral fish biomass in two fishing seasons, namely the west and east seasons. The results of the study, reef fish biomass in the two seasons is relatively different. The difference between the two is due to different fishing patterns, wherein the wet season, the reef fish that are targeted by fishermen are the Serranidae and Lutjanidae families, and the size of the fish is relatively large by using hooks number 5, 6, 7 and 8. In contrast, in the east season, the target fish fishers are all reef fishes and are relatively small in size using hooks 15, 16 and 17. The problem is that some fishermen still use explosives in catching reef fish. Muis et al. (2019) reported the condition of live coral cover in the coastal waters of the Spelman Strait in moderate condition (37.71) and dead coral (33.71). Community participation in the management of fisheries resources is significant to note because the community is the user of these resources. Community participation in the management of fisheries resources is crucial to do because of fishermen as users of resources. Muis et al. (2019) reported the condition of live coral cover in the coastal waters of the Spelman Strait in moderate condition (37.71) and dead coral (33.71).